INTEGRASI AKHLAK ISLAMI DALAM SENI TEATER - Rimasasi, Dwi Suryani; Astutik, Anita Puji (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2021)
Morals are about character and behavior which are reflected and embedded in a person. Therefore, everyone must have Islamic morals to avoid themselves from any negative influences. During this time, the integration of Islamic morals has only been carried out in certain subjects. While it is known that Islamic morals are the most important thing for students to equip themselves, especially in theater related to appreciation and creation. This research aims to analyze efforts in optimizing the integration of Islamic morals in theater. The method this research belongs to field research. This research is expected to create Islamic morals in students which are not only about knowledge, but also about the implementation and reflection in everyday’s lives.